Special Issue: Islet Inflammation and Metabolic Homeostasis - Susan J. Burke; J. Jason Collier (Metabolites, 2021)
This special issue was commissioned to offer a source of distinct viewpoints and novel data that capture some of the subtleties of the pancreatic islet, especially in relation to adaptive changes that influence metabolic homeostasis [...]